IMPLEMENTASI PROGRAM LAYANAN DUKUNGAN PSIKOSOSIAL (LDP) PASCABENCANA (STUDI PADA BADAN PENANGGULANGAN BENCANA DAERAH PROVINSI DAERAH KHUSUS IBUKOTA JAKARTA) - Rangga Bima Setiawan; Harits Hijrah Wicaksana; Surryanto Djoko Waluyo; Agung Edi Rustanto (Jurnal Academia Praja, 2026)
This study focuses on how post-disaster psychosocial support services provided by the regional disaster management agency in the Special Region of Jakarta Province are utilized. The extent to which this program has successfully helped the mental recovery of disaster-affected communities is the issue under study. The purpose of this study was to identify the methods for implementing the program, the obstacles encountered, and the program's impact on the beneficiary community. A qualitative descriptive approach was used in this study, with data collected through documentation, direct observation, and in-depth interviews. The results indicate that the psychosocial support service program has helped restore the community's emotional and social well-being, but challenges remain with cross-agency coordination, limited workforce, and program sustainability.